Risk of Bacterial Infection from Proton Pump Inhibitor Use - Sung Soo Kim; Yunju Jo; Seun Ja Park; Jeong Seop Moon; Dong Ho Lee; Jae Jun Kim; Yong Chan Lee; Ethics and Education Committee of Korean College of Helicobacter and Upper Gastrointestinal Research (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Currently, proton pump inhibitors are used in a wide range of patients with gastroesophageal reflux disease, peptic ulcer, and upper gastrointestinal symptoms such as dyspepsia. In addition, the application of proton pump inhibitors for prevention of gastrointestinal complications induced by non-steroidal anti-inflammatory drugs is expected to increase their use in the future. The use of proton pump inhibitors promotes bacterial growth by reducing gastric acid concentration. If the acidity (pH) of the stomach fluid is lower than 4, most pathogens can be sterilized. However, patients who need to use a proton pump inhibitor should maintain a gastric acidity of at least 5 or 6, and can be at risk of infections such as pneumonia and Clostridium difficile infection. Several infectious diseases associated with the use of proton pump inhibitors were reviewed.